Awareness towards Environmental Pollution and Academic Achievement among Secondary Level Students in Purba Bardhaman District of West Bengal, India - Dhara, Ranajit; Amarnath Das (MultiTech Publisher, 2024)
The main purposes of the study were to elucidate the levels of awareness towards environmental pollution and academic achievement and to investigate the relationship between awareness towards environmental pollution and academic achievement, the factors that affect awareness towards environmental pollution was determined. Awareness towards environmental pollution measuring questionnaires were done with 188 secondary levels students of Bardhaman district. For the analysis of data, Mean, S.D., ‘t’ test, ANOVA, and graph have been applied in itself. The moderate level of awareness towards environmental pollution and academic achievement both have been observed in present study. It is revealed that the Girls and Urban students were comparatively more aware towards environmental pollution than Boys and Rural. Non-minority students were comparatively more aware towards environmental pollution than Minority. Through the present study, it was also found that there is no significantly difference among various part of Parent’s Occupation, Family’s Economical Status and Categories. But on the basis of mean scores, Sons of Serviceman, Rich Family and Unreserved category are more aware towards Environmental Pollution than others.